ADHERENCE TO LONG-TERM TREATMENT OF CARDIOVASCULAR DISEASE AND NON-COMPLIANCE WITH MEDICAL RECOMMENDATIONS: THE OPINION OF PATIENTS AND PHYSICIANS BY THE RESULTS OF FOCUSED INTERVIEW - O. N. Semenova; E. A. Naumova; Yu. G. Schwartz (Столичная издательская компания, 2015)
Aim. To study the subjective opinion of patients and doctors about their individual experiences with adherence to treatment for chronic cardiovascular diseases in the group focused interview of patients and their physicians. Material and methods. 3 groups of patients from clinical studies adhering to the doctor's recommendations (focus-group 1) and 3 groups of patients hospitalized for cardiovascular events, not adhering to recommendations after discharge (focus-group 2) and one focus-group of doctors were analyzed. Group discussion was performed by a moderator (experienced sociologist, with no medical training who was not familiar with the patients and physicians). Results. 47 patients (25 (53.2 %) men and 22 (46.8%) women) and 6 doctors participated in the study. Paternalistic model of communication with doctors present in the minds of all patients. In patients of the first group this results in a full confidence in the doctor and compliance with all recommendations while in patients of the second group lack of care in the outpatient clinic makes them "offended" by the underestimation of their trust and causes non-compliance. Physicians intuitively divide patients into less and more "attractive" for themselves. This "division" on the one hand may have some predictive value in respect of patients' adherence to a further treatment, and on the other hand, the "doctors' prejudice" in relation to the patient may adversely effect the behavior of the patients and failure to follow the recommendations in the future. Conclusion. The significant paternalism on the part of the patient on the one hand increases the responsibility of the physician for his patient, and on the other hand - increases opportunities for his influence on the patients' behavior.